Accentuating the Positive? - Fineman, Stephen (Academy of Management Review, 2006)
In my critique of positiveness I raised a number of key concerns about the conceptualization and development of the positive perspective in organizational behavior and organizational studies. Roberts addresses some of my worries, but still leaves open some importance questions, in particular the ontological assumptions that underpin positiveness and the scope for embracing critical theory.